Double Aortic Arch A Case Study - Afroze, Jahan; Samin, Musavvir (Cardiovascular Journal, 2017)
Double aortic arch (DAA) is one of the 2 most common forms of vascular ring, a class of congenital anomalies of the aortic arch system in which the trachea and esophagus are completely encircled by connected segments of the aortic arch and its branches. The aim of this study is to describe a case of DAA in a middle aged person. A 40 year old male came to outdoor patient department with cough and breathlessness since childhood which was diagnosed earlier as bronchial asthma, cold allergy, and dust allergy. The final diagnosis DAA was made after CT angiogram. Establishing a diagnosis of DAA in a middle aged person requires thorough understanding and clinical skills in performing steps. Cardiovasc. j. 2017; 10(1): 91-93